Shouldering the burden : water conservation campaigns and the question of responsibility - Bütüner, Gizem. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
This thesis tackles the questions of what water is and why water conservation campaigns blame individual actions for water scarcity while agricultural and industrial uses of water are much more than household use. The two questions are approached through a critical discourse analysis of the existing literature on water and Finish’s water footprint campaign called Yarının Suyu. The first part explores the changing meanings of water in society, politics, economics, and the environment, arguing that water is an abstract hybrid with an intrinsic value as the subject in its encounters with others rather than a mere object as a resource or commodity. After establishing various meanings of water to different sets of people, the thesis uncovers why individuals are accused in water footprint campaigns, arguing that such campaigns regard water as a commodity to be profited from in contrast to their claims of water as a right to protect. Engaging with these two broad themes, this thesis criticizes an anthropocentric approach and the binary of nature/culture, arguing that water and society are internally related, transforming and being transformed in their relations. As such, it traces the global water crisis back to humanity, which can only be resolved by people changing their mindsets regarding water from a resourcist one to acknowledging its intrinsic value. The thesis concludes that only if we can change how we value water by not putting the responsibility on individuals and by making production and supply more sustainable, can we solve the water crisis.
Keywords: Water conservation -- Case studies.